Analisis SOAR Strategi Pemasaran Pembiayaan Pembelian Kendaraan Guna Menarik Minat Anggota di BMT Aman Utama Jepara - Adi, Ahmad; Fauzan Mubarok, Ahmad (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to determine the marketing strategy for vehicle purchase financing products at BMT Aman Utama Jepara through SOAR (Strength, Opportunities, Aspiration, Results) analysis. This research uses descriptive qualitative research methods. The results of this research explain that BMT Aman Utama Jepara implements a marketing strategy that refers to the marketing mix such as product, price, place and promotion. The results obtained from SOAR analysis on the marketing strategy for financing the purchase of BMT Aman Utama Jepara vehicles are in quadrant II, namely the S-R strategy by using the strengths they have to achieve the desired results. The following are the results of the combination of S-R strategies including: 1.) providing easy financing with minimal fines, 2.) implement effective promotions by providing discounts and rewards, 3.) providing access to online services such as official websites or Fintech applications.